RETRACTED: Physio-metabolic and clinical consequences of wearing face masks—Systematic review with meta-analysis and comprehensive evaluation - Kisielinski, Kai; Hirsch, Oliver; Wagner, Susanne; Wojtasik, Barbara; Funken, Stefan; Klosterhalfen, Bernd; Kanti Manna, Soumen; Prescher, Andreas; Sukul, Pritam; Sönnichsen, Andreas (Frontiers in Public Health, 2023)
Background: As face masks became mandatory in most countries during the COVID-19 pandemic, adverse effects require substantiated investigation. Methods: A systematic review of 2168 studies on adverse medical mask effects yielded 54 publications for synthesis and 37 studies for meta-analysis (on n=8641, m=2482, f=6159, age=34.8±12.5). The median trial duration was only 18 min (IQR=50) for our comprehensive evaluation of mask induced physio-metabolic and clinical outcomes. Results: We found significant effects in both medical surgical and N95 masks, with a greater impact of the second. These effects included decreased SpO2 (overall Standard Mean Difference, SMD= -0.24, 95%CI= -0.38 to -0.11, p<0.001) and minute ventilation (SMD= -0.72, 95%CI=- 0.99 to -0.46, p<0.001), simultaneous increased in blood-CO2 (SMD= +0.64, 95%CI= 0.31–0.96, p<0.001), heart rate (N95: SMD= +0.22, 95%CI= 0.03–0.41, p=0.02), systolic blood pressure (surgical: SMD= +0.21, 95%CI= 0.03–0.39, p=0.02), skin temperature (overall SMD= +0.80 95%CI 0.23–1.38, p=0.006) and humidity (SMD +2.24, 95%CI= 1.32–3.17, p<0.001). Effects on exertion (overall SMD= +0.9, surgical= +0.63, N95=+1.19), discomfort (SMD= +1.16), dyspnoea (SMD= +1.46), heat (SMD= +0.70) and humidity (SMD= +0.9) were significant in n=373 with a robust relationship to mask wearing (p<0.006 to p<0.001). Pooled symptom prevalence (n=8128) was significant for: headache (62%, p<0.001), acne (38%, p<0.001), skin irritation (36%, p<0.001), dyspnoea (33%, p<0.001), heat (26%, p<0.001), itching (26%, p<0.001), voice disorder (23%, p<0.03) and dizziness (5%, p=0.01). Discussion: Masks interfered with O2-uptake and CO2-release and compromised respiratory compensation. Though evaluated wearing durations are shorter than daily/prolonged use, outcomes independently validate mask-induced exhaustion-syndrome (MIES) and down-stream physio-metabolic disfunctions. MIES can have long-term clinical consequences, especially for vulnerable groups. So far, several mask related symptoms may have been misinterpreted as long COVID-19 symptoms. In any case, the possible MIES contrasts with the WHO definition of health. Conclusion: Face mask side-effects must be assessed (risk-benefit) against the available evidence of their effectiveness against viral transmissions. In the absence of strong empirical evidence of effectiveness, mask wearing should not be mandated let alone enforced by law.